Intelligent smoke detector with evacuation routing / Mohamad Lokman Zahari & Nabila Aiman Noor Hamidy - Zahari, Mohamad Lokman; Noor Hamidy, Nabila Aiman (2015)
Intelligent Smoke Detector With Evacuation Routing which this project will help the citizen to take the first step to safe their life from fires. This project will help the citizen to evacuate the building by showing the direction to exit the building with LED stripe. The smoke detector will detect a smoke, the buzzer and LED stripe will turn on in the same time to alert people from the fire burning in the building. This will make easier for fire department to evacuate the building and control the fire before the fire spread to other place. When the fire is stop burning there is no smoke to detect. Therefore, the smoke detector will turn off automatically.